Physical Environmental Conditions and Germ Number in Bedroom of Tuberculosis Patients in Kupang City, East Nusa Tenggara Province - Wanti Wanti; Agustina Agustina; Siprianus Singga; Titik Respati (Global Medical & Health Communication (GMHC), 2022)
The ability of Mycobacterium tuberculosis as the agent of tuberculosis (TB) to live in the air is generally very dependent on environmental factors, which can cause bacteria to last long in the air and increase the risk of transmission of TB. The research purpose was to analyze the relationship between the physical environment condition and the number of germs in the bedroom of TB patients. This cross-sectional research was conducted in Kupang city, East Nusa Tenggara province, in January–June 2022 with 77 TB patients as samples, whose TB patients' rooms would be observed based on research variables for physical environmental conditions. Data were collected directly by observing and measuring directly from the variables studied and then analyzed using a correlation test and linear regression test to see the relationship between variables and the effect of the physical environmental condition on germ number in the bedroom. The correlation test shows the variables related to the bedroom germ number (p<0.25) were the number of people sleeping the TB patients, lighting, humidity, ventilation size, percentage of ventilation compared to room size, and room density. The model equation explains that 28.8% of the germ number variation in bedroom TB patients depends on the constant reduction (789,884) added to 19,217 times the bedroom humidity, then reduced by 9,518 times the percentage of room ventilation and also reduced by 31,185 times the density of the room occupancy. The most significant influence on the germ number in TB patients' bedrooms is the room humidity, which is 0.319.